2015
DOI: 10.1227/neu.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vascular Anatomy on the Formation of Basilar Tip Aneurysms

Abstract: Larger posterior cerebral artery angles and smaller basilar artery diameters are associated with the formation of basilar tip aneurysms. These parameters are easily measurable by the clinician and will aid in screening strategies in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Furthermore, aneurysm neck size overestimation due to 3D RA can lead to significantly different WSS results and a different flow structure classification. Other groups reported that the vascular anatomy has the greatest influence on the development of IA and subsequent rupture,21 22 whereas other factors such as viscosity play only a minor role 23 24. However, these results are based on a small number of IAs and must therefore be considered with caution.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, aneurysm neck size overestimation due to 3D RA can lead to significantly different WSS results and a different flow structure classification. Other groups reported that the vascular anatomy has the greatest influence on the development of IA and subsequent rupture,21 22 whereas other factors such as viscosity play only a minor role 23 24. However, these results are based on a small number of IAs and must therefore be considered with caution.…”
Section: Discussionmentioning
confidence: 90%
“…It has been previously demonstrated that the geometry of the affected arteries can contribute to the formation of the IA, independent of familial contributions. 2,[6][7][8]12,15,18,39 Specifically, the anatomy of the anterior complex of the CW can create a trend toward the formation of IAs in the ACoA. 16 Indeed, IAs form preferentially at arterial bifurcations and on tight vascular curvatures (having a low radius of curvature).…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with sporadic aneurysms, the effect of specific anatomical variations within the circle of Willis (CW) on the formation of IA has been well established. 2,[6][7][8]16 The purpose of this study was to investigate specific anatomical variations within the anterior communicating artery (ACoA) complex that may be significantly associated with the presence of IAs. For this purpose we compared anatomical and structural characteristics of the ACoA complex, such as asymmetry and angle measurement, in 3 groups: patients with a familial ACoA aneurysm (FACAA), patients with a sporadic ACoA aneurysm (SACAA), and healthy first-degree relatives (HFDRs) of FACAA patients.…”
mentioning
confidence: 99%
“…Kayembe et al ,16 found no increased incidence of fPCA in the aneurysm group compared with controls, but only four of the 44 aneurysms studied involved the basilar tip. More recently, Can et al ,10 found that a smaller BA diameter and a larger P1–P1 angle were associated with a higher incidence of BTA, but anatomical variants of the circle of Willis were not assessed. Campos et al ,18 identified P1 agenesis in 2.8% of 47 patients with BTA, but hypoplastic P1 segments were not assessed and no data on the prevalence of those variants in individuals without BTA were given.…”
Section: Discussionmentioning
confidence: 99%
“…Established modifiable risk factors include smoking, alcohol consumption, and hypertension,1–3 but genetic predisposition is also an important factor 2 4. Hemodynamic forces also play a major role in aneurysm formation, enlargement, and rupture, with wall shear stress and transmural pressure linked to mechanical and molecular changes,4–9 triggering focal degenerative mechanisms at the vessel wall 10. Accordingly, saccular aneurysms are most commonly located at branching points of the major arteries, where hemodynamic stress is highest 5…”
Section: Introductionmentioning
confidence: 99%